Double Disadvantages: A Study of Ethnic and Hukou Effects on Class Mobility in China (1996–2014) - Li, Yaojun (2017)
This paper examines the ethnic and household registration system (hukou) effects on intergenerational social mobility for men in China. Using national representative surveys covering almost two decades (1996–2014), we assess both absolute and relative rates of mobility by ethnicity and hukou origin. With regard to absolute mobility, we find that minority men had significantly lower rates of total and upward mobility than Han men, and those from rural hukou origins faced more unfavourable chances. With regard to relative mobility, we find men of rural ethnic origins significantly less likely to inherit their parental positions. Even with parental and own educational qualifications and party memberships controlled for, we still find ethnic minority men of rural hukou origins behind others in access to professional-managerial positions. Overall, our findings suggest that the preferential policies have largely removed the ethnic differences in the urban sector but ethnic minority men from rural hukou origins are faced with double disadvantages: in addition to the inequality of opportunity rooted in the institutional divide which they share with the majority group from similar backgrounds, they face much greater inequalities in conditions, namely, in having poorer socio-economic and cultural resources.